ARTIFICIAL INTELLIGENCE, LEGAL PERSONHOOD AND INTELLECTUAL PROPERTY RIGHTS: NAVIGATING THE NEW FRONTIER OF CREATION - Lal, Sahil; Singh, Bhupinder (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial intelligence and its implications are reshaping traditional legal contexts - especially in the context of intellectual property rights (IPRs) and the emerging debate on legal personhood. Now that machines are capable of self-generation, invention and authorship, issues of ownership, liability, and legal personhood beg to be answered. This article examines the shifting terrain which AI-generated content is now creating for human-based IPR regimes. It explores the possibility that legal personhood for AIs offers a workable means of attributing rights and responsibilities or an incoherent one that challenges the agency and ethical requirements of the law. Through a comparison of laws, analysis of technology, and analysis of policy, the research seeks to engage penetratingly with discussions about the interplay of innovation and regulation in this novel space of creation. The results are intended to inform future legal reforms, and set a framework for fair, accountable, and innovative AI in the future.